Chamber investigation of the formation and transformation of secondary organic aerosol in mixtures of biogenic and anthropogenic volatile organic compounds - Aristeidis Voliotis (16563090) (2022)
Abstract A comprehensive chamber investigation of photochemical secondary organic aerosol (SOA) formation and transformation in mixtures of anthropogenic (o-cresol) and biogenic (α-pinene and isoprene) volatile organic compound (VOC) precursors in the presence of NOx and inorganic seed particles was conducted. To enable direct comparison across systems, the initial concentration (hence reactivity) of the systems towards the dominant OH oxidant was adjusted. Comparing experiments conducted in single-precursor systems at various initial reactivity levels (referenced to a nominal base case VOC concentration, e.g. halving the initial concentration for a 1/2 initial reactivity experiment) as well as their binary and ternary mixtures, we show that the molecular interactions from the mixing of the precursors can be investigated and discuss challenges in their interpretation. The observed average SOA particle mass yields (the organic particle mass produced for a mass of VOC consumed) in descending order were found for the following systems: α-pinene (32 ± 7 %), α-pinene–o-cresol (28 ± 9 %), α-pinene at 1/2 initial reactivity (21 ± 5 %), α-pinene–isoprene (16 ± 1 %), α-pinene at 1/3 initial reactivity (15 ± 4 %), o-cresol (13 ± 3 %), α-pinene–o-cresol–isoprene (11 ± 4 %), o-cresol at 1/2 initial reactivity (11 ± 3 %), o-cresol–isoprene (6 ± 2 %), and isoprene (0 ± 0 %). We find a clear suppression of the SOA mass yield from α-pinene when it is mixed with isoprene, whilst no suppression or enhancement of SOA particle yield from o-cresol was found when it was similarly mixed with isoprene. The α-pinene–o-cresol system yield appeared to be increased compared to that calculated based on the additivity, whilst in the α-pinene–o-cresol–isoprene system the measured and predicted yields were comparable. However, in mixtures in which more than one precursor contributes to the SOA particle mass it is unclear whether changes in the SOA formation potential are attributable to physical or chemical interactions, since the reference basis for the comparison is complex. Online and offline chemical composition as well as SOA particle volatility, water uptake, and “phase” behaviour measurements that were used to interpret the SOA formation and behaviour are introduced and detailed elsewhere. Other Information Published in: Atmospheric Chemistry and Physics License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5194/acp-22-14147-2022